A intenção da adoção de comportamento sexual seguro entre doadores de sangue : enfoque na prevenção de HIV/AIDS - Barbosa, Stella Maia (2011)
This study aims to analyze the intention of safe sexual behavior among blood donors from the Blood Center of Fortaleza, Ceara, through their perception of risk and vulnerability to HIV and adoption of sexual behavior to reduce risk. This is a cross-sectional and exploratory study with 384 blood donors from the Blood Center of Fortaleza, using data collection from a self-administered questionnaire. The resulting data were presented by associations between knowledge, intention and behavior of blood donors with their characteristics and analyzed using X2 test or maximum likelihood. The open questions were organized into thematic categories, analyzing them qualitatively. There was male predominance with 72.1% of the sample, participants' average age of 32 years, 94.3% live in Fortaleza or Metropolitan Region; 78.4% had high school or higher educational level and an average monthly income of two minimum wages. It is noticed that still prevails equivocal knowledge about modes of transmission of HIV, but 50.2% of respondents answered incorrectly or did not know if the virus was transmitted in public restrooms and 6% of blood donors responded or mistakenly left in doubt whether the virus was transmitted by mosquitoes. Regarding the number of sexual partners, blood donors have an average of 1.5 partners per year. Preventive strategies against the risk of HIV transmission were evaluated and the condom is used regularly by 13.1% of donors in relations with regular partners and 47.6% when the partner is considered possible. According to the classification of Mann in relation to the vulnerability of the subject sample thus behave: 6.3% of donors fall into the group of least vulnerability for reporting no sexual activity, while 86.9% of donors blood are classified as high vulnerability because they have a unique partnership and does not use condoms consistently. It can be inferred from this study that the participants had a high vulnerability to HIV infection, which is not expected for a profile of blood donors, because the implications of this result may bring in transfusion safety. Therefore, we suggest the deployment of the health activities related to prevention of STD/AIDS, culturally sensitive and targeted to blood donors because they have social and civil liability when making the choice to donate their blood for those who need it. In this aspect, Nurses must include health education activities with blood donors, because they are increasingly working in the field of Hematology and taking an active role in contributing to improving the quality of transfused blood products for the Brazilian population.